2005
DOI: 10.1177/104063870501700418
|View full text |Cite
|
Sign up to set email alerts
|

Endometritis and Cystic Endometrial Hyperplasia in a Goat

Abstract: Abstract. Histologic examination was performed on uterine biopsy samples of irregular cystic masses noted during caesarean section of a 2-year-old female Boer goat. Histopathologic examination revealed multifocal erosions of the superficial epithelium and multifocal infiltration of the endometrium by widely scattered viable and degenerate neutrophils, lymphocytes, and plasma cells admixed with mild amounts of cellular debris and hemorrhage. The endometrium was markedly expanded by many irregular cystic and hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…Inflammatory cell infiltration such as neutrophils, lymphocytes, and macrophages in endometrial tissue was an indicator of endometrial inflammation in Aceh cattle with RB caused by subacute and chronic bacterial infection. [26] stated that inflammatory cell infiltration in goats with endometritis shows the categories of inflammation, namely acute, subacute, and chronic phases. In the acute phase, neutrophils could be found in the caruncle, intercaruncular, and uterine glands.…”
Section: Resultsmentioning
confidence: 99%
“…Inflammatory cell infiltration such as neutrophils, lymphocytes, and macrophages in endometrial tissue was an indicator of endometrial inflammation in Aceh cattle with RB caused by subacute and chronic bacterial infection. [26] stated that inflammatory cell infiltration in goats with endometritis shows the categories of inflammation, namely acute, subacute, and chronic phases. In the acute phase, neutrophils could be found in the caruncle, intercaruncular, and uterine glands.…”
Section: Resultsmentioning
confidence: 99%
“…Cystic endometrial hyperplasia or glandular endometrial cysts are consequences of hormonal disorders, especially hyperestrogenism, which are rare in ruminants and more common in cats and dogs [37,38]. This pathology differs from the endometrial cysts, which are primarily found in senile mares, as a result of lymphatic obstruction associated with fibrosis and dilatation [37,39]. In ruminants, these complications are usually related to the constant and prolonged intake of phytoestrogens, which are present in poisonous plants and can also be produced by fungi [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the relevance of reproductive diseases for the bovine dairy industry, the bulk of literature on puerperal endometritis or metritis has focused on cattle diseases, 10,11,17,23 with fewer reports dedicated to small ruminants. 20 In goats, acute puerperal metritis (APM) is characterized by a dark red, malodorous uterine discharge, and complicated cases may result in peritonitis, involving agents such as Staphylococcus aureus , Pasteurella sp., and coliforms. 14,23 As in other ruminants, APM is typically preceded by an abnormal parturition due to twin births, dystocia, placental retention, or trauma of the birth canal.…”
Section: Introductionmentioning
confidence: 99%